Consumption Smoothing and the Current Account : Evidence for France, 1970-1994 - Bismut, Claude (IMF Working Papers; Working Paper, 1995)
This paper estimates a simple consumption-smoothing model of the French current account, and examines its capacity to predict recent developments in France's external performance. The model views the current account as a buffer through which private agents can smooth consumption over time in response to temporary disturbances to output, investment, and government expenditure. The empirical results indicate that the model performs well overall, and predicts correctly the sharp turnaround in France's external accounts observed in the past three years-a feature of the data that conventional models of trade flows, based on income and relative price variables, appear unable to explain.